Perspektif Filsafat Hukum terhadap Kepailitan dan Keadilan Bagi Pekerja Dalam Kasus Sritex - Rasji; Doni Hafendi (CV Rewang Rencang, 2024)
This study aims to examine the application of justice and legal certainty principles in the bankruptcy process of PT Sritex from a legal philosophy perspective. The research method used is normative juridical with statutory, case, and philosophical analysis approaches. The discussion reveals that although positive law mandates the protection of workers' rights, in practice there is a disparity in prioritizing secured creditors over workers. Legal epistemology highlights how legal knowledge in the Sritex case tends to favor economic power over substantive justice for vulnerable groups. Court decisions are seen as neglecting distributive justice and overlooking the humanistic dimension of law enforcement. The theory of legal certainty becomes crucial as the bankruptcy process causes uncertainty among workers and creditors regarding their rights. Satjipto Rahardjo's progressive law approach argues that law should side with the weak, calling for reform in the bankruptcy mechanism toward social justice. In conclusion, Indonesia’s bankruptcy system must be reformed to strengthen worker protection through fair debt settlement schemes and regulations that ensure inclusive legal certainty.